Análise semiótica peirciana aplicada em capas de livros infantis - CARNEIRO, Ellen Santos (2022)
This paper is about the Peirce semiotics analyse which treats the signs and their relations. The main goal is to aplly the semiotics theory on two children book covers related to the death. The research is relevant becuase of the fenomenal which can be anlised and considered a sign, sice there is meaning and sense production to the one who will understand. This way, the methodology is based on Peirce (2005), Santaella (2004), Coelho Netto (1980), Foucault (1988) e Marcuschi (2007). the object will be two chieldren book covers which were analised semiotically acoording to the Peirce categories, focusing on the second division of the sign related to its object: Iconical, indicial and simbolical aspects.